Can Problem Based Learning Models Improve Students' Mathematical Problem-Solving Ability? - Asdar, Fajriani; Yusuf, St. Fatimah; Wijaya, Nirwan Arif Indah; Mustafa, Sriyanti (Universitas Muhammadiyah Surakarta, 2023)
This research was motivated by the low problem-solving abilities of students, especially on the indicators of understanding the problem and checking back on the answers obtained. This research is classroom action research, which aims to improve students' mathematical problem-solving abilities through the Problem Based learning model. The subjects of this research were 35 students in class X 4 of SMAN 1 Sinjai, SMP Negeri 1 Patampanua class VII.5, totaling 26 people, and SMP Negeri 1 Mattirosompe class VIII.1, totaling 22 people. This research was carried out in two cycles. The research work procedure for each cycle takes place in four stages, namely: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting. Data collection was carried out by giving problem solving tests to students. The data was analyzed using quantitative and qualitative analysis. Based on the results of the research and discussion, it can be concluded that the application of the Problem Based Learning learning model in two different phases in three schools can improve students' mathematical problem-solving abilities. After carrying out 2 learning cycles using Problem learning, it was found that the level of mathematical problem-solving ability for each indicator met the minimum criteria of 65%, and students' classical problem-solving completeness reached 100%.